Trends in incidence and associated risk factors of suicide mortality in patients with non‐small cell lung cancer - Zhou, Huaqiang (Cancer Med, 2018)
Lung cancer patients have an increased risk for committing suicide. But no comprehensive study about the suicide issues among non‐small‐cell lung cancer (NSCLC) patients has been published. We aimed to estimate the trend of suicide rate and identify the high‐risk group of NSCLC patients. Patients diagnosed with primary NSCLC were identified from Surveillance, Epidemiology, and End Results (SEER) database (1973‐2013). Suicide mortality rate (SMR) were calculated. Multivariable logistic regression was employed to find out independent risk factors for suicide. Among 495 889 NSCLC patients, 694 (0.14%) of them died from suicide. The suicide mortality rates have significantly decreased (before 1993: 0.21%, 1994‐2003: 0.16%, after 2004: 0.09%, P < .001). Male (OR 6.22, 95% CI: 4.96‐7.98, P < .001), white (OR 3.89, 95% CI: 2.66‐5.97, P < .001), being unmarried (OR 1.43, 95% CI: 1.22‐1.67, P < .001), the elderly (60‐74 vs <60: OR 1.24, 95% CI: 1.03‐1.50, P = .024, >75 vs <60: OR 1.31, 95% CI: 1.05‐1.63, P = .018) were independently associated with higher risk of suicide mortality. Surgery (OR: 1.44, 95% CI: 1.19‐1.73, P < .001) was also relative with higher risk of suicide. Our study observed significant decrease in suicide mortality among NSCLC patients in US over past decades. Older age, male sex, unmarried status, and surgery were risk factors of committing suicide. Clinicians should be aware of these high‐risk groups.